2023
DOI: 10.15376/biores.18.1.1454-1464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam explosion treatment on impregnation of three species of softwoods: North American spruce, Korean pine, and Japanese larch

Abstract: Effects of steam explosion were investigated relative to impregnation of wood. Three types of softwoods [North American spruce (Picea orientalis), Korean pine (Pinus koraiensis), and Japanese larch (Larix kaempferi)] were prepared and subjected to steam explosion treatment. The cross-sectional surfaces of the samples were observed with SEM, and their open-pore and closed-pore porosities were determined using a gas pycnometer. The softwoods were vacuum impregnated using ACQ-2 (Alkaline Copper Quaternary), a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The vacuum pressure impregnation process can be optimized by adjusting the flow characteristics of the chemical, chamber temperature, and impregnation pressure and time. Jang and Kang [21] reported that, among various variables in the vacuum pressure impregnation process, pressure was a significant variable in improving the impregnation of wood.…”
Section: Introductionmentioning
confidence: 99%
“…The vacuum pressure impregnation process can be optimized by adjusting the flow characteristics of the chemical, chamber temperature, and impregnation pressure and time. Jang and Kang [21] reported that, among various variables in the vacuum pressure impregnation process, pressure was a significant variable in improving the impregnation of wood.…”
Section: Introductionmentioning
confidence: 99%